Evaluasi Implementasi Kurikulum Merdeka: Studi Literatur Mengenai Dampak terhadap Motivasi dan Hasil Belajar Siswa - Siti Wulan Sari; Siti Farkha’i; Jalaludin Jalaludin (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Indonesia's educational transformation faces complex challenges in preparing a generation capable of competing in the global era. This research examines the implementation of the Merdeka Curriculum as a strategic response to 21st-century learning needs through a systematic literature review approach. The study focuses on three fundamental aspects: policy implementation practices across various educational institutions, identification of supporting and inhibiting factors in learning transformation, and evaluation of impacts on student competency improvement. The research method employs a qualitative approach with content analysis techniques on scientific literature from 2021-2025 sourced from national and international journals and official policy documents from the Ministry of Education, Culture, Research, and Technology. Data analysis was conducted through content analysis techniques encompassing reduction, data presentation, and conclusion drawing. Findings reveal that Merdeka Curriculum implementation successfully integrates 4C skills through project-based learning and differentiation that accommodates diverse student characteristics. Principal leadership, teacher competency, and Platform Merdeka Mengajar support emerge as key success elements, while infrastructure limitations, inter-regional digital gaps, and human resource readiness remain significant obstacles. Positive impacts are evident in improved student literacy and numeracy, character strengthening through the Pancasila Student Profile, and teacher role transformation from teacher-centered to student-centered approaches. This research recommends strengthening continuous mentoring systems, equalizing access to learning technology, and affirmative policies for disadvantaged areas to accelerate inclusive and quality educational transformation throughout Indonesia.